Left Ventricular Diastolic Dysfunction in β-Thalassemia Major with Heart Failure. (2nd January 2018) - Mancuso, Luigi; Vitrano, Angela; Mancuso, Andrea; Sacco, Massimiliano; Ledda, Antonietta; Maggio, Aurelio
Abstract: We studied the clinical, electrocardiographic, echocardiographic, Doppler and T2* cardiac magnetic resonance (CMR) data of all adult β-thalassemia major (β-TM) patients with heart failure (HF) consecutively observed at our referral center of the Sicilian region between 2008 and 2016. There were 16 patients enrolled in the study. Echocardiographic examination showed that only one patient had HF with systolic dysfunction of the left ventricle (HFrEF), whereas the others had HF with preserved systolic function of the left ventricle (HFpEF). Systolic dysfunction of the right ventricle (RV) was observed in 13 cases. Furthermore, 30.0% of the patients presented T2* CMR values consistent with intermediate risk of systolic dysfunction of the left ventricle (LV) due to iron overload, whereas 70.0% had normal values. Typical electrocardiographic abnormalities (wide T wave inversion and low voltages) were observed in 11 out of 16 patients. In conclusion, in the adult β-TM patients with HF recently observed at our center, the predominant form was that with diastolic dysfunction of the LV, and with systolic dysfunction of the RV. Only 30.0% had low values of T2* CMR. Typical electrocardiographic abnormalities were found in 69.0%.